Novel aspects of regulatory T cell dysfunction as a therapeutic target in giant cell arteritis. Issue 1 (28th September 2021) - Adriawan, Ignatius Ryan; Atschekzei, Faranaz; Dittrich-Breiholz, Oliver; Garantziotis, Panagiotis; Hirsch, Stefanie; Risser, Linus Maximillian; Kosanke, Maike; Schmidt, Reinhold Ernst; Witte, Torsten; Sogkas, Georgios
Abstract : Objectives: Giant cell arteritis (GCA) is the most common primary vasculitis, preferentially affecting the aorta and its large-calibre branches. An imbalance between proinflammatory CD4 + T helper cell subsets and regulatory T cells (Tregs) is thought to be involved in the pathogenesis of GCA and Treg dysfunction has been associated with active disease. Our work aims to explore the aetiology of Treg dysfunction and the way it is affected by remission-inducing immunomodulatory regimens. Methods: A total of 41 GCA patients were classified into active disease (n=14) and disease in remission (n=27). GCA patients' and healthy blood donors' (HD) Tregs were sorted and subjected to transcriptome and phenotypic analysis. Results: Transcriptome analysis revealed 27 genes, which were differentially regulated between GCA-derived and HD-derived Tregs. Among those, we identified transcription factors, glycolytic enzymes and IL-2 signalling mediators. We confirmed the downregulation of forkhead box P3 (FOXP3) and interferon regulatory factor 4 (IRF4) at protein level and identified the ineffective induction of glycoprotein A repetitions predominant (GARP) and CD25 as well as the reduced T cell receptor (TCR)-induced calcium influx as correlates of Treg dysfunction in GCA. Inhibition of glycolysis in HD-derived Tregs recapitulated most identified dysfunctions of GCA Tregs, suggesting the central pathogenic role of the downregulation of the glycolytic enzymes. Separate analysis of the subgroup of tocilizumab-treated patients identified the recovery of the TCR-induced calcium influx and the Treg suppressive function to associate with disease remission. Conclusions: Our findings suggest that low glycolysis and calcium signalling account for Treg dysfunction and inflammation in GCA.